Answer:
-x+6
Step-by-step explanation:
3(x+2)-4x
3x+6-4x
-x+6
Answer:
x=15
Step-by-step explanation:
crown plz
Answer:
12x + 18y + 6z + 4x - 4z
Step-by-step explanation:
Given the expression : 3(4x + 6y + 2z) + 4(x – z)
To eliminate the parenthesis ; we use the distributive property :
3(4x + 6y + 2z) + 4(x – z) becomes ;
3*4x + 3*6y + 3*2z + 4*x + 4*-z
12x + 18y + 6z + 4x - 4z
Hence,
12x + 4x + 18y + 6z - 4z
16x + 18y + 2z
24 = 2 x 12, 24 = 8 x 3, 24 = 6 x 4, draw factor trees that all show 24 = 2 x 2 x 2 x 3 at the end.
Pls give me a brainliest if this helped thx